Understanding the Challenges, Yet Focusing on the Successes: An Investigation into Indigenous University Students’ Academic Success - Lydster, Cameron; Murray, Jason (The Australian Journal of Indigenous Education, 2019)
This paper reports on experiences of Indigenous students and staff involved in Bond Indigenous Tutoring (BIT). It aimed to gain insight regarding topics including challenges faced by Indigenous students, why some students discontinued their studies, and concepts of success at university. Findings revealed the main challenges included the transition from secondary to tertiary education and not being prepared academically. BIT staff identified family responsibilities and being dislocated from kinship networks as challenges, while students stated these were factors explaining why Indigenous students discontinued their studies. A whole of university approach was found to be required to effectively support Indigenous students. Success was defined as more than Grade Point Average, as it entailed being able to enjoy future endeavours. This paper contributes to the evidence that tuition programmes and Indigenous centres at university are key contributors to success, and it is argued that such success must become the norm as opposed to the exception.